Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
9514 1404 393
Answer:
(A, B, C) = (-1, 2, 2)
Step-by-step explanation:
Simplify the right side and equate coefficients of the x-terms.
x² -3 = A(x² +1) +(Bx +C)(x -1)
x² -3 = Ax² +A +Bx² -Bx +Cx -C
x² -3 = (A+B)x² +(C-B)x +(A-C) . . . . identify coefficients of each x-term
Matching coefficients on the left and right gives rise to three equations in the three unknowns:
A +B = 1
C -B = 0
A -C = -3
Adding all three equations, we get ...
(A +B) +(C -B) +(A -C) = (1) +(0) +(-3)
2A = -2
A = -1 . . . . . . divide by 2
B = 1 -A = 2
C = B = 2
The coefficients are ...
(A, B, C) = (-1, 2, 2)
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.